Association between the use of protease inhibitors in Highly Active Antiretroviral Therapy (HAART) and incidence of diabetes mellitus in HIV-infected patients: A systematic review and meta-analysis - Chanamé-Baca, Diego (2018)
Introduction: Despite the advances in increasing life expectancy among people living with HIV/AIDS, Highly Active Antiretroviral Treatment (HAART) use and HIV infection itself have been associated with the occurrence of Type 2 Diabetes Mellitus (DM), specifically with the use of protease inhibitors (PIs). The aim of this systematic review was to determine if there is an association between the use of PIs and the incidence of DM in HIV-infected patients. Methods: A systematic literature search was performed using MEDLINE/PubMed, CENTRAL, LILACS and EMBASE. Included articles were observational studies published on or prior to November 2015 that met the following criteria: study population comprised HIV-infected patients aged 18 years or older and who were receiving HAART; patients assessed according to their use of PIs; DM were defined in the study and described during follow-up. Studies were selected independently by two investigators. Pooled relative risks (RR) and hazard ratios (HR) were calculated. Heterogeneity was assessed by New Castle Ottawa Scale (NOS) for nonrandomized studies and The Cochrane Collaboration’s Tool for assessing risk of bias for randomized trials. Results: 13155 HIV patients in 6 studies were included. All studies used HR as association measure and only 1 study used RR. Length of follow-up varied between 3 years to 17 years. No association between the use of PIs and development of DM was found: the HR for the incidence of DM among patients using PIs was 1.23 (95% CI 0.66 to 2.30; p-value: 0.51) and the RR was 1.25 (95% CI 0.99 to 1.58; p-value 0.06). Conclusion: No evidence of an increased risk of DM was found. However, the length of follow-up could be short to evaluate DM incidence, requiring a longer follow-up in order to detect an association between PI use and onset of DM.